Ordenando el Almuerzo (Ordering Lunch). Vocational Branch, Food Services. Teacher's and Student's Booklets, First Edition - Dade County Public Schools, Miami, FL.; Dade County Public Schools, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The materials in this program are written to individualize the teaching of Spanish to English speakers, and are designed to provide as much flexibility as possible for both the teacher and student. The materials can be used for large groups, small groups, and individual work, although direct teacher-student contact is considered to be beneficial. This package is focused on a conversation about "ordering lunch." The materials included in the package are a teacher's booklet, a student's booklet, and tapes. The teacher's booklet contains specific instructions, the written copy of the taped oral presentation of the material, answer keys, a vocabulary list, and bibliographic references, as well as the full content of the student's booklet. The student's booklet contains two sections. Section A is comprised of oral presentations, listening comprehension and speaking tests, reading and writing exercises and tests. Section B contains four "cursillos" (learning modules), which include performance objectives, pictures, self-check tests, listening sheets, and silent reading and writing exercises. (LG)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiolingual Skills; Audiovisual Aids; English; Individualized Instruction; Instructional Materials; Language Instruction; Language Programs; Listening Comprehension; Programed Instructional Materials; Second Language Learning; Spanish; Tape Recordings; Textbooks; Individualizing Spanish for Speakers of English; Books